Experimental study on combined valorization of bituminous coal derived fluidized bed fly ash and carbon dioxide from energy sector. (15th February 2023) - Zdeb, Janusz; Howaniec, Natalia; Smoliński, Adam
Abstract: Carbon dioxide mineralization using alkaline earth metals rich waste, offers the opportunity of a combined utilization of captured carbon dioxide and valorization of burdensome waste. Most of the studies reported refer to the utilization of steel slags or combustion products of coal and petcoke blends, lignite, municipal waste or air pollution control system residues from conventional boilers. Indirect wet and direct dry carbonation methods under elevated pressure and/or temperature are mostly considered. Within this paper, the results of the experimental study on a dry, direct carbonation method with the use of bituminous coal derived fluidized bed fly ash and performed under ambient conditions are presented. The porous structure parameters of the process product, missing from the existing literature, are analyzed. Therefore, the study differs from the existing literature in terms of the carbonation method used, alkaline earth metals source, scale of the experiment, process conditions employed and product parameters studied. The efficiency of carbon dioxide uptake of 0.008–0.054 kgCO2 /kg was proven to be comparable with reported for more energy- and cost-intensive methods. The development of porous structure of the process product was also demonstrated with up to several fold increase in the specific surface area and the total pore volume. Highlights: Bituminous coal fluidized bed fly ash as a valuable source of alkaline earth metals. Valorization of bituminous coal fluidized bed fly ash combined with CO2 utilization. Beneficial modifications of porous structure of carbonated fluidized bed fly ash. Efficiency comparable to more complex, energy- and cost-intensive carbonation methods.